Guest

X sin cube theta +y cos cube theta =sin theta cos theta and x sin theta - y cos theta=0 . Then xsquare + y square

X sin cube theta +y cos cube theta =sin theta cos theta and x sin theta - y cos theta=0 . Then xsquare + y square

Question Image
Grade:10

1 Answers

Arun
25758 Points
4 years ago
xsin3? + ycos3? = sin?cos? 
 
and xsin?=ycos? 
 
Put this value in above equation we get
 
xsin3? + xsin?cos2? = sin?cos? 
xsin?(sin2? + cos2?) = sin?cos? 
x=cos?
so y=sin?
 
hence x2 + y2 = sin2? + cos2? = 1
 
Option B is correct

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free